The adventures of Captain Underpants - Pilkey, Dav, 1966- (2013)
When George and Harold hypnotize their principal into thinking that he is the superhero Captain Underpants, he leads them to the lair of the nefarious Dr. Diaper, where they must defeat his evil robot henchmen.
"Now in full color."
Originally published: New York : Blue Sky Press, ©1997.
Accelerated Reader AR
Reading Counts RC
Accelerated Reader
Keywords: Captain Underpants (Fictitious character) -- Juvenile fiction; School principals -- Juvenile fiction; Heroes -- Juvenile fiction; Humorous fiction; Fiction; Humorous fiction -- Juvenile; Juvenile works; Science fiction; Humorous fiction